Prove by Mathematical Induction? : # sum_(k=0)^n x^k = (1-x^(n+1)) / (1-x) #
1 Answer
We aim to prove by Mathematical Induction that for
# sum_(k=0)^n x^k = (1-x^(n+1)) / (1-x) #
When
# LHS = sum_(k=0)^n x^k = x^0 + x^1 = 1 +x #
# RHS = (1-x^2)/(1-x) = ( (1+x)(1-x) ) / (1-x) = 1 + x#
So the given result is true when
Now, Let us assume that the given result is true when
# sum_(k=0)^m x^k = (1-x^(m+1)) / (1-x) #
Adding the next term of the sum gives us:
# sum_(k=0)^(m+1) x^k = (sum_(k=0)^(m) x^k ) + x^(m+1) #
And using the above assumption, we have:
# sum_(k=0)^(m+1) x^k = (1-x^(m+1)) / (1-x) + x^(m+1) #
# " " = (1-x^(m+1) + (1-x)x^(m+1))/(1-x) #
# " " = (1-x^(m+1) + x^(m+1) + x x^(m+1))/(1-x) #
# " " = (1 + x x^(m+1))/(1-x) #
# " " = (1 + x^(m+2))/(1-x) #
# " " = (1 + x^((m+1)+1))/(1-x) #
Which is the given result with
So, we have shown that if the given result is true for
Hence, by the process of mathematical induction the given result is true for
Supporting Note
The above result should come as no surprise because:
# sum_(k=0)^n x^k = x^0+x^1+x^2 + ... + x^n #
Which are the
First Term
#a=x^0=1# ,
Common Ratio#r=x#
And so, using the GP formula, the sum of the first
# S_n = a(1-r^n)/(1-r) #
# \ \ \ \ = 1(1-x^(n+1))/(1-x) \ \ \ # (remember we have#n+1# terms)
# \ \ \ \ = (1-x^(n+1))/(1-x) # QED